Development of a Sensing Platform Based on Hands-Free Interfaces for Controlling Electronic Devices - Rojas, Mario; Ponce, Pedro; Molina, Arturo (Frontiers in Human Neuroscience, 2022)
Hands-free interfaces are essential to people with limited mobility for interacting with biomedical or electronic devices. However, there are not enough sensing platforms that quickly tailor the interface to these users with disabilities. Thus, this paper proposes to create a sensing platform that could be used by patients with mobility impairments to manipulate electronic devices, thereby their independence will be increased. Hence, a new sensing scheme is developed by using three hands-free signals as inputs: voice commands, head movements and eye gestures. These signals are obtained by using non-invasive sensors: a microphone for the speech commands, an accelerometer to detect inertial head movements and an infrared oculography to register eye gestures. These signals are processed and received as the user’s commands by an output unit, which provides several communication ports for sending control signals to other devices. The interaction methods are intuitive and could extend boundaries for people with disabilities to manipulate local or remote digital systems. As a study case, two volunteers with severe disabilities used the sensing platform to steer a power wheelchair. Participants performed 15 common skills to wheelchairs users and their capacities were evaluated according to a standard test. By using the head control they obtained 93.3% and 86.6%, respectively for volunteers A and B; meanwhile by using the voice control they obtained 63.3% and 66.6%, respectively. These results show that the end-users achieved high performance by developing most of the skills by using the head movements interface. On the contrary, the users were not able to develop most of the skills by using the voice control. These results showed valuable information for tailoring the sensing platform according to the end-user needs.